Cellular and molecular influencers of neuroinflammation in Alzheimer's disease: Recent concepts & roles - Ghosh P.; Singh R.; Ganeshpurkar A.; Pokle A.V.; Singh S.K.; Kumar A. (My University, 2025)
Alzheimer's disease (AD), an extremely common neurodegenerative disorder of the older generation, is one of the leading causes of death globally. Besides the conventional hallmarks i.e. Amyloid-β (Aβ) plaques and neurofibrillary tangles (NFTs), neuroinflammation also serves as a major contributing factor in the pathogenesis of AD. There are mounting evidences to support the fundamental role of cellular (microglia, astrocytes, mast cells, and T-cells) and molecular (cytokines, chemokines, caspases, and complement proteins) influencers of neuroinflammation in producing/promoting neurodegeneration and dementia in AD. Genome-wide association studies (GWAS) have revealed the involvement of various single nucleotide polymorphisms (SNPs) of genes related to neuroinflammation with the risk of developing AD. Modulating the release of the neuroinflammatory molecules and targeting their relevant mechanisms may have beneficial effects on the onset, progress and severity of the disease. Here, we review the distinct role of various mediators and modulators of neuroinflammation that impact the pathogenesis and progression of AD as well as incite further research efforts for the treatment of AD through a neuroinflammatory approach. © 2021 Elsevier Ltd